Hubungan Dukungan Keluarga dengan Kualitas Hidup Penderita Diabetes Melitus - Tomi Agustias Aryanto; Sulastyawati Sulastyawati; Nurul Pujiastuti; Nurul Hidayah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Diabetes mellitus is often called the silent killer because this disease attacks the majority of the sufferer's organs which can cause complaints and complications that affect the quality of life. Supporting factors that can affect the quality of life of people with diabetes is family support. This study aimed to determine the relationship between family support and the quality of life of people with diabetes mellitus in the working area of the Polowijen Health Center. The research design used a cross-sectional study. The sampling technique uses probability sampling with cluster random sampling specifications with a total of 46 respondents. Data processing using the Pearson test. The results of the Pearson test showed that there was a relationship between family support and quality of life for people with diabetes mellitus with a p-value significance value of (0.000), which means that there is a relationship between family support and quality of life for people with diabetes mellitus with a large correlation (0.836) which means that the correlation is very strong.